Dampak Pergeseran Mata Pencaharian terhadap Kehidupan Lingkungan: Kajian Bibliometrik - Chrisanthy Yessda Matital; Hasbi Hasbi; Sultan Sultan (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
This study maps research on livelihood shifts and their environmental implications through a secondary bibliometric analysis of metadata processed with Bibliometrix/R Studio. The analysis covers 139 documents published between 1981 and 2026 from 124 publication sources and examines publication growth, document types, productive sources and affiliations, influential documents, three-field relations, and keyword co-occurrence. The findings show that the literature is organized around the intersection of economic impact, development, poverty, employment, mining, land use, climate change, and sustainable development. The study contributes conceptually by positioning livelihood shifts as a socio-ecological transition that links changes in work and income with environmental pressures and adaptive development pathways. Because the analysis uses a processed bibliometric output, the study also clarifies the limits of data verification and applies consistency checks across bibliometric indicators, tables, and visual maps to strengthen interpretive reliability.